A New Model of Repetitive Traumatic Brain Injury in Mice - Chen, Kui; Gu, Hao; Zhu, Liang; Feng, Dong-Fu (Frontiers in Neuroscience, 2020)
Repetitive traumatic brain injury (rTBI) is a major health care concern that causes substantial neurological impairment. To better understand rTBI, we introduced a new model of rTBI in mice induced by sudden rotation in the coronal plane combined with lateral translation delivered twice at an interval of 24 h. By routine histology, histological examination of Prussian blue-stained sections revealed the presence of microbleed in the corpus callosum and brain stem. Amyloid precursor protein (β-APP) and neurofilament heavy-chain (NF-200) immunohistochemistry demonstrated axonal injury following rTBI. Swelling, waving, and enlargement axons were observed in the corpus callosum and brain stem 24 h after injury by Bielschowsky staining. Ultrastructural studies by electron microscopy provided further insights into the existence and progression of axonal injury. rTBI led to widespread astrogliosis and microgliosis in white matter, as well as significantly increased levels of tumor necrosis factor (TNF)-α and interleukin (IL)-1β. rTBI mice showed a significantly increased loss of righting reflex (LRR) duration within each time point compared with that of sham animals, which was under 15 min. rTBI mice exhibited depression-like behavior at 1 month. rTBI mice also demonstrated deficits in MWM testing. These results suggested that this model might be suitable for investigating rTBI pathophysiology and evaluating preclinical candidate therapeutics.